Racial Discrimination in Tourism: The Record of Apartheid Cape Town - Rogerson, Christian M.; Rogerson, Jayne M. (Modern Geográfia)
This article contributes to international scholarship on racial discrimination in tourism, a literature dominated by studies on the United States which concentrate on the segregation era of Jim Crow. It is argued the segregation of tourism and hospitality spaces for ‘non-Whites’ in apartheid South Africa parallels the USA during the Jim Crow years. The study focuses on the 1960s decade when the implementation of apartheid measures was at its most intense. The research uses archival sources to document racial discrimination occurring in tourism in the setting of apartheid Cape Town. Evidence is given of the minimal infrastructure of accommodation services for ‘non-White’ travellers, constraints imposed by influx control and visitor permits on the mobilities of Africans, racially segregated hospitality spaces for eating, the near total absence of options for organized leisure tours of the city, and petty apartheid restrictions on access by ‘non-Whites’ to certain places of interest. Racial discrimination was imprinted also on the racialized landscape of beaches and the unwelcoming quality of beach spaces allocated to ‘non-Whites’.